Two new species of Rykellus (Acari: Mesostigmata: Ologamasidae) from Brazil and a key to the world species of the genus - Santos, Jandir C. [UNESP]; Castilho, Raphael C. [UNESP]; Silva, Edmilson S.; De Moraes, Gilberto J. (Magnolia Press, 2015)
Rykellus anibali n. sp. and Rykellus mineiroi n. sp. are described from adult females and males collected from litter and soil in the state of Sao Paulo, Brazil. A key for the identification of females of the eight recognisable world species of Rykellus is provided.
Keywords: Soil mites; Rhodacaroidea; Taxonomy